2018
DOI: 10.3390/nu10050603
|View full text |Cite
|
Sign up to set email alerts
|

Association of Habitually Low Intake of Dietary Calcium with Blood Pressure and Hypertension in a Population with Predominantly Plant-Based Diets

Abstract: This study aimed to assess the association of habitually low dietary calcium intake with blood pressure or hypertensive risk using data from the China Health and Nutrition Survey (CHNS) in 2009. We included 6298 participants (2890 men and 3408 women) aged 18 years or older in this analysis. Food intakes were measured by 3-day 24-h individual recalls combined with a weighing and measuring of household food inventory. The participants were divided into normotensive, pre-hypertensive and hypertensive groups accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
2
4
1
Order By: Relevance
“…Here, we found an increased hypertension risk in the UP; however, we observed no significant associations in the RP. Similarly, Ziqi et al found no significant association between DCI and hypertension in Chinese adults [22]. In our rural group, we identified a non-conclusive association of hypertension occurrence and DCI.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Here, we found an increased hypertension risk in the UP; however, we observed no significant associations in the RP. Similarly, Ziqi et al found no significant association between DCI and hypertension in Chinese adults [22]. In our rural group, we identified a non-conclusive association of hypertension occurrence and DCI.…”
Section: Discussioncontrasting
confidence: 51%
“…In the above-mentioned Cochrane study, there was no alteration effect of the calcium supplementation on the diastolic blood pressure [19]. A recent cohort study conducted in Chinese populations indicated inconclusive results on the consumption of calcium related to blood pressure or the risk of hypertension [22]. A prospective cohort study in 28,886 middle-aged and older women by Wang and colleagues showed a lower rate of hypertension in participants with high calcium consumption (1679 mg/day) (RR 1.12, 95% CI 1.05-1.20), while participants over 45 years of age with low calcium consumption (<558 mg/day) had a higher rate of hypertension [23].…”
Section: Introductionmentioning
confidence: 94%
“…Among studies reviewed for the relationship between Ca intake and blood pressure ( Table 6 ), the effect of Ca intake on the decrease in blood pressure was more significant in women compared to men [ 49 56 57 58 ]; however, there were also results that did not show significant positive effects in both women and men [ 43 49 53 ]. A cohort study found that the conjoint effects of serum Ca and insulin resistance at baseline on hypertension at follow-up [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, to our knowledge, little is known about the association of dietary calcium, magnesium, and phosphorus intakes with stroke incidence in the Chinese population. The average dietary intake of these micronutrients among Chinese individuals consuming predominantly plant-based diets was reported to be lower than that of Europeans and Americans who have more dairy and meat products 15 . In this context, a large-scale prospective study in the Chinese population to supplement the association's evidence is admittedly needed.…”
Section: Introductionmentioning
confidence: 87%